A note on large cardamom (Amomum subulatum Roxb.) germplasm collection - NAIDU, Y S RAO, U GUPTA, ANAND KUMAR, R (Journal of Spices and Aromatic Crops, 1993)
Eleven accessions (SBLC 1-11) of large cardamom (Amomum subulatum) collected from Sikkim and Darjeeling di strict of West Bengal, India were studied for some morphological attributes. SBLC 11 (Barlanga variety) had superior yielding characters like 4 spikes per tiller and bold size of capsules with 45-46 seeds.